Mentoring the Mentor: Tales from Learning the Practice of Field-Based Teacher Education - Patricia Norman (Networks: An Online Journal for Teacher Research, 2004)
While completing my doctorate at Michigan State University, I served as a university liaison in its five-year teacher certification program. Teacher candidates enter the program as juniors, take two years of courses combined with field experiences then complete a year-long internship with a single classroom teacher who accepts primary responsibility for guiding and assessing interns' learning. Interns are placed in small cohorts of six to eight per school. University liaisons -- typically MSU graduate students -- work with interns at a single school and help them set personal learning goals, confer with them and their mentors about their planning and teaching, offer feedback, and formally assess them at mid-term and end-of-semester conferences.